O DIREITO CONSTITUCIONAL INTERNACIONAL E A SUA RELAÇÃO COM O CONCEITO DE SOBERANIA ESTATAL - HENRIQUES, ANA C. A.; SULZBACH, CAMILA C.; VIEIRA, GUSTAVO O.; CARMO, JULIANA S. D.; PENNA, LUCIANA R.; ROSA, RUBIENA A. (Salão do Conhecimento, 2013)
Resumo